PRODUCTION OF BIO-BTX FROM EMPTY FRUIT BUNCHES: DEVELOPMENT OF AROMATIZATION CATALYST OVER ZEOLITE-BASED CATALYST - LUTHFI (NIM: 23016043), MUHAMMAD
Aromatic compounds, especially benzene, toluene, and xyline is an important chemical in the petroleum refining industry. BTX compounds can be used as feedstock for the petrochemical industry and as the important basic compound in the development of high-end chemicals such as polyethylene terephtalate (PET) and Nylon-66. Alternative renewable resource which are environmentally benign are increasingly attracting attention due to increasing energy demands and the limitaion of fossil fuels. Empty fruit bunches (EFB) can be used in producing BTX compounds by catalytic fast pyrolysis. This research aims to develop catalyst capable of processing empty fruit bunches into bio-BTX. The catalyst used is a zeolite Y and ZSM-5, which was placed in a fixed bed reactor. The variation investigated in this research including the feedstock (IPA, hexane, GVL, and p-cresol), metal (Fe, Zn, and Mg), Ã‚Â¬metal-loading (1%-5%), and NaOH concentration (0,3 M, 0,5 M, dan 0,8 M). The results showed that zeolite Y and ZSM-5 can be used for converting various types of feed into aromatic products (BTX) by carrying out various reactions, i.e. dehydration, decarbonylation, decarboxylation, oligomerization and isomerization reactions. The best catalyst for converting GVL feed were HZSM-5 which gave a yield an selectivity BTX respectively of 4,57%-C and 5,11%-A. The addition of lignin in GVL solvent can increased the yield and selectivity of BTX product, the yield from 2,88%-C to 5,50%-C and the selectivity from 5,79%-A to 7,66%-A. The greater the concentration of lignin in the GVL solvent then the yield and selectivity of the BTX product were also be greater. Addition of metals (Fe, Zn, Mg) can increased zeolite activity, especially on HZSM-5 catalyst with the highest yield and selectivity BTX product produced by Zn metals, 25,80%-C and 27,71%-A. Desilication treatment using NaOH in HZSM-5 catalyst did not provide a good effect, thus decreasing the yield and selectivity of BTX product.